INFORMATION WANTS AND INFORMATION SEEKING ACTIONS FROM PORTUGUESE NEUROLOGIST: INVESTIGATIVE ASSORTED TECHNIQUE RESEARCH - Barreto, Amilcar; Jose Sá, Maria; Luzeiro, Isabel (Health and Society, 2024)
Background: Medical professionals nowadays must be well-versed in the most recent, scientifically confirmed facts on illness diagnosis, treatment, and patient care. Despite the fact that there are an increasing number and variety of information sources available to physicians, many questions remain concerning the authenticity, quality, and usefulness of medical information. With the goal of improving current medical information delivery, new methodologies are needed to assess doctors’ real-life demands. Objective: The goal of this study was to explore the information requirements and seeking behaviour of Portuguese’s neurologists treating patients with multiple sclerosis (MS) and migraine. Methods: An exploratory mixed methods (quantitative and qualitative) investigation of 15 consecutive days was conducted. It was necessary to recruit a total of 50 neurologists (25 MS experts and 25 migraine specialists). An instant messaging programme built for this study was used to gather data. Personal interviews were conducted by computer at each information-seeking session, which included semi structured interviews and closed-ended questions. Content analysis was used to identify emergent themes from the mobile app interactions and physician enquiries. Results: A total of 36/20, or 71 percent, of the questions posed by neurologists were linked to treatment management and pharmacological information, followed by diagnostic techniques and procedures. Online resources were preferred by doctors (48/50, 96 percent) over offline alternatives (24/50, 47 percent) in a quantitative study. In 33% of information-seeking activities, a multi-channel strategy was used, which included using both online and offline resources to address the same demand. Neurologists were more likely to use internet resources than offline ones (F=1.7; P=.01) to get information. Compared to migraine neurologists, MS specialists were 53% more likely to participate in a single information-seeking event (risk ratio 1.54; 95% CI 1.12 to 2.05). More than two-thirds of MS specialists (28 percent [7/25] vs. 10 percent [2/25], P=.06) were interested in patient-related material, whereas migraine physicians (85% [21/25] vs. 60% [15/25], P=.05) were more inclined to seek information on treatment management. Both online and offline information searching was more difficult for migraine experts (F=12.5, P=.01) and offline channels were utilised less often (30 percent [8/25] versus 60 percent of information-seeking events, P=.02). To get information from various sources, both migraine and MS experts reported lower satisfaction rates (single source vs multiple sources P=.003). Conclusion: Portuguese MS and migraine neurologists are described in great depth in this research, including their real-life search activity as well as educational requirements and information sources they use. Neurologist information demands and information-seeking behaviour are influenced by their professional field. Identifying the temporal and context-specific demands of physicians is essential for designing a successful medical information strategy, according to these results.